Starch from quinoa and amaranth flour for potential food applications: Thermal, electrokinetic and spectral characterization of the water-based starch extract - Muchekeza, Jane Tafadzwa; Nantanga, Komeine Kotokeni Mekondjo; Itenge, Theopoline Omagano; Moyo, Mambo (Journal of Food Technology Research, 2025)
Quinoa and amaranth are pseudo-cereals suitable as cereal alternatives due to their potential use in functional foods. The study investigated the physicochemical properties of quinoa, amaranth, and water-extracted starches. Characterization of the flours and starches was performed using electrochemical analysis, differential scanning calorimetry, thermogravimetric analysis, powder X-ray diffraction, UV-Vis spectrometry, and Fourier Transform Infrared spectroscopy. The electrochemical analysis results indicated that extracted starches and flours are suitable electron acceptors in fermented foods. Thermal analysis by differential scanning calorimetry showed endothermic peaks of AMF (92.70 °C) > AMS (90.52 °C) > QF (84.83 °C) > CS-WFM (83.56 °C) > QS (70.41 °C), which depicted a variation in gelatinization temperatures. Fourier transform infrared spectroscopy analysis showed bands similar for all starches and flours. X-ray diffraction analysis of the powder showed different crystallinity patterns, indicating the presence of an A-type crystalline structure. UV-Vis spectrophotometry displayed peaks of 337 and 341 nm for amaranth and quinoa starch, respectively, and the quinoa peak is similar to a wide peak (340–354 nm) demonstrated by corn starch (reference). The results underline the diverse properties of quinoa, amaranth, and corn starch and indicate their potential as functional ingredients in various food applications.